Analisis kritis konsep tsiqah dalam ilmu hadis sebagai fondasi pendidikan karakter Islami - Saefuddin, A'raf (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This research critically examines the concept of tsiqah in hadith science and its relevance as an essential foundation for Islamic character education. In the modern era, the urgency of fostering individuals with integrity and credibility has become vital. In the Islamic tradition, the validity of hadith heavily relies on tsiqah, which encompasses two main pillars: ‘adalah (moral integrity, honesty) and dhabt (accuracy, meticulousness). Utilizing a qualitative approach and library research, this study analyzes classical hadith literature and Islamic character education studies. It finds that the values inherent in tsiqah, such as honesty, trustworthiness, meticulousness, and responsibility, are not only relevant for hadith authentication but also form the core of Islamic character. This concept offers a rich pedagogical framework, where the figure of a tsiqah narrator can serve as a role model, and the principles of hadith verification can be adapted into learning methods that cultivate critical, responsible, and credible character in students. Thus, this research concludes that tsiqah is a solid foundation for shaping Muslim individuals who are not only knowledgeable but also possess moral integrity and can be trusted within society.